Whither the state? On Santi Romano's The legal order. Issue 2 (30th August 2018) - Croce, Mariano
ABSTRACT: This essay foregrounds the relevance of Italian jurist Santi Romano's theorizing to today's political and legal debates on the relation between state and non-state laws. As Romano's classic book L'ordinamento giuridico (1917–1918) has finally been translated into English, the Anglophone readership can take stock of one of the most enlightening contributions to institutional thinking in the last centuries. Romano put forward a theory of legal institutionalism that has legal pluralism as a basic corollary and contended that the legal order is naturally equipped to temper and overcome conflicts between bodies of law. The present contribution argues that this approach unravels the riddles of recent multiculturalist paradigms and provides invaluable insights on the way the state could and should manage the conflicts between competing normative orders that lay claims to legislative and jurisdictional autonomy.